Study Abroad and Adult Education: Broadening the Discourse and Exploring the Development of a Just Framework - Susan M. Yelich Biniecki (Adult Education Research Conference, 2013)
The purpose of this proposed paper is to examine the current dialogue surrounding study abroad and adult education, broaden the discourse, and propose starting points for conceptualizing a just framework.